Islamic Education Model in Madrasah in The Perspective of Islamic Education Philosophy - Mirza Mahbub Wijaya (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
Madrasah is an Islamic educational institution that is unique in Indonesia. On this fact, this study tries to explore the philosophical foundation of the existing system in madrasah. This research is a literature review. Data analysis uses a descriptive analysis method and philosophical approach. This study results concluded that the Islamic education system in madrasah has three philosophical foundations, namely ontology, epistemology, and axiology. The ontology dimension shows the existence of madrasah as tafaqquh fi al-din to instill the principles of akidah akhlak. In terms of epistemology, madrasah prioritize religiosity as a scientific development. In the axiological dimension, Islamic education aims to develop people who are oriented towards the afterlife.